Experimental corrections in neutron scattering experiments: A modern theoretical and computational approach - Dawidowski, Javier; Rodriguez Palomino, Luis Alberto; Blostein, Juan Jeronimo; Cuello, Gabriel Julio (Taylor & Francis, 2014)
Fil: Dawidowski, Javier. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina